Parallel Optimisation Strategies for Fusion Codes - Jackson, Adrian; Reid, Fiona; Booth, Stephen; Hein, Joachim; Westerholm, Jan; Aspnäs, Mats; Catala, Miquel; Soba, Alejandro (19th International Euromicro Conference on Parallel, Distributed and Network-Based Processing (PDP 2011), Ayia Napa, Cyprus, 2011-02-09 - 2011-02-11, 2011)
We have previously documented the on-going work in the EUFORIA project to parallelise and optimise European fusion simulation codes, see. This involves working with a wide range of codes to try and address any performance and scaling issues that these codes have. However, as no two simulation codes are exactly the same, it is very hard to apply exactly the same approach to optimising a disparate range of codes. Indeed, it can be seen from that the codes investigated range in terms of performance and ability from well-optimised, highly parallelised codes, to serial or poorly performing codes. After analysing, optimising, and parallelising a range of codes it is, actually, possible to discern a number of distinct optimisation techniques or approaches/strategies that can be used to improve the performance or scaling of a parallel simulation code. This paper outlines the distinct approaches that we have identified, highlighting their benefits and drawbacks, giving an overview of the type of work that is often attempted for fusion simulation code optimisation.
Keywords: optimisation; fusion; HPC; parallelisation